127 Increasing engagement in student feedback in the clinical years. (16th November 2020) - Mostafa, Omar; Malik, Amman; Shah, Haroon
Abstract : Background: At the University of Birmingham, cohorts' student representatives ('Academic Representatives' - AR) are viewed as the intermediaries between staff and students; they represent views of the cohort, express concerns and work closely with the staff to tackle issues across all aspects of the medicine programme, academic and wellbeing. Obtaining feedback is therefore instrumental in identifying student concerns and views and relaying them to the staff. While this is simpler in pre-clinical years where students are primarily at the university, obtaining feedback becomes difficult in the clinical years due to students being placed at various hospital sites across the West Midlands. In the academic year 19/20, students in Year 4 had their feedback collected using feedback forms distributed electronically by the Year 4 AR. In contrast, the Year 3 cohort had their views represented in the form of designated hospital representatives which fed back to the Year 3 AR. Aim: To assess the effectiveness of using hospital representatives in representing feedback compared with feedback forms. Method: For Year 4, we used the number of feedback responses registered throughout the academic year. For Year 3, we relied on the qualitative responses gained from hospital representatives, alongside feedback from senior medical school staff. Results: For feedback forms, there were 65 responses (cohort of 340) in the 19/20 academic year. This is markedly lower than the 185 responses recorded in 15/16 academic year. For hospital representatives, the senior staff found the feedback provided to be more in-depth, practical and purposeful. Also, students found engagement with the hospital representatives more welcoming than using feedback forms. Conclusion: Deployment of hospital representatives across different placement sites has proved to be more efficacious and practical. We recommend this to be implemented on a larger scale across other avenues.